"It's the Economy, Stupid": Strategies for Improved Cost Containment in Cancer Treatment. Issue 4 (10th January 2014) - Sleijfer, S
<x xml:space="preserve">Abstract</x> The advent of numerous novel antitumor compounds has improved the prognosis of many cancer patients but has also substantially increased the costs of cancer care and put more pressure on health‐care budgets. This situation increasingly raises questions such as the extent to which these drugs offer value sufficient to justify their cost and how to accommodate the increasing costs of cancer care. Here I look at the various aspects that affect cancer care economics and offer potential solutions. Clinical Pharmacology & Therapeutics (2014); 95 4, 365–367. doi:10.1038/clpt.2014.9